Maslahah Sebagai Kerangka Berfikir Dan Tujuan Hukum Islam - Ririn Fauziyah; Agus Sholahudin Shidiq; Burhanatut Dyana (ASASI: Journal of Islamic Family Law, 2021)
Islamic law came with the realization of the mission and the maximization maslahah and elimination and minimization madarrah. In fact, there are frequently used the slogan, "Where there is a law of God's where maslahah and wherever maslahah that's where the law of God". Once the close of Islamic law with maslahah, the scholars use maslahah as istinbat method, source, and destination of Islamic law. Lately to unveil the veil on a law prescribed destination is because there are elements of the benefit in it. Once the urgency maslahah that sometimes appears the statement that the possibility of a benefit will remain high even though contrary to scriptures, either Nas al-Qur'an, Hadith, and ijma '. Maslahah is looking good and benefit and avoid mafsadah (damage). Maslahah able to collaborate with other disciplines within the law establishes a case. Of note, the benefit of which is contained in it qualifies maslahah that could be used as evidence. For instance, cooperation between maslahah with medical science in the matter of abortion. Where basically the legal origin of abortion is prohibited, but because there is a greater benefit of the legal origin of abortion can be shifted into even sometimes required when there is a greater benefit in it